Internship Programs at Bank Syariah Indonesia in Improving Competence Student Accountancy - Rizkina, Miftha; Aliah, Nur; Dayu, Wulan (Accounting and Business Journal, 2024)
Study This aims to find out the role of the internship program at BSI for student accounting at Panca Budi Development University . Research This using qualitative data that is the data collected from source direct from object under study . Data sources used is primary data through interview direct to the intended party . Data analysis techniques using analysis descriptive that is analyze the data obtained that is results from interview to the intended party Then make the right conclusion . The result of study is that from interviews conducted​ to the 4 students who carried it out internship at BSI, student get Lots benefits , good That experience , knowledge , and everything related to the world of work , activities apprenticeship is means improvement and development level Universities make it responsible student​ responsible , independent and skilled when jump in the world of work . Students know difference between conventional banks and Islamic banks, knowing practice Islamic banking and products offered by Islamic banks. Training public speaking skills with give service to Customer in a way directly . From the results interview This can concluded that internship at BSI can increase competence Good soft skills and also hard skills from student accountancy .